Photo-induced semimetallic states realised in electron–hole coupled insulators. Issue 1 (December 2018) - Okazaki, Kozo; Ogawa, Yu; Suzuki, Takeshi; Yamamoto, Takashi; Someya, Takashi; Michimae, Shoya; Watanabe, Mari; Lu, Yangfan; Nohara, Minoru; Takagi, Hidenori; Katayama, Naoyuki; Sawa, Hiroshi; et al.
Abstract Using light to manipulate materials into desired states is one of the goals in condensed matter physics, since light control can provide ultrafast and environmentally friendly photonics devices. However, it is generally difficult to realise a photo-induced phase which is not merely a higher entropy phase corresponding to a high-temperature phase at equilibrium. Here, we report realisation of photo-induced insulator-to-metal transitions in Ta2 Ni(Se1−x Sx )5 including the excitonic insulator phase using time- and angle-resolved photoemission spectroscopy. From the dynamic properties of the system, we determine that screening of excitonic correlations plays a key role in the timescale of the transition to the metallic phase, which supports the existence of an excitonic insulator phase at equilibrium. The non-equilibrium metallic state observed unexpectedly in the direct-gap excitonic insulator opens up a new avenue to optical band engineering in electron–hole coupled systems. Ultrafast light pulses can manipulate and probe materials faster than relaxation timescales, leading to new electronic states and insights into equilibrium properties. Okazaki et al. use the properties of photo-induced metallic states to investigate unconventional correlated behaviour in Ta2 NiSe5 and Ta2 NiS5 .